THE EFFECT OF CONTEXTUAL COMIC STRIP ON EIGHTH GRADE STUDENTS’ READING COMPREHENSIONAT SMP NEGERI 6 SINGARAJA - M.Y., Sosiawan; A.A.I.N., Marhaeni; N.L.P.E.S.D., Dewi (Universitas Pendidikan Ganesha, 2019)
The main objective of this experimental study was to investigate whether there is a significant effect of contextual comic strips strategy on students reading comprehension. The study was conducted at the eighth-grade students of SMP Negeri 6 Singaraja. This Posttest-Only Control group design was applied. The population in this study was all of the students at SMP Negeri 6 Singaraja in the academic year 2018/2019. The sample in this study was 60 students consisting of 30 students from the VIII B1 class as the experimental group and 30 students from VIII B2 as the control group. The sample was selected by using cluster random sampling technique. The data were collected through a post-test in the form of multiple-choice test. The data were analyzed by using t-test in SPSS 16.0 program. The result of this study revealed that the mean score for the experimental group (73.17) is higher than the control group (69.00). The result of the t-test also showed that the value of Sig. (2-tailed) was 0.025. Since the value of Sig. (2-tailed) was below 0.05, the null hypothesis was rejected and the alternative hypothesis was accepted. Based on the result, it can be concluded that there was a significant effect of Contextual Comic Strips on eighth-grade students? reading comprehension at SMP Negeri 6 Singaraja in the academic year 2018/2019.